KEDUDUKAN HUKUM PENGURUS PERSEROAN SEBAGAI PENANGGUNG PAJAK: Legal Position Of The Management Of The Company As Tax Bearer - I Gede Yudi Arsawan; Dian Purnamasari; Rini Purwaningsih (Jurnal Hukum PRIORIS, 2023)
In carrying out the governance of a nation, there are expenses necessary for the expenditures of the state, some of which are obtained through tax revenues collected from individuals classified as taxpayers. However, not all taxpayers fulfill their tax payments on time, and sometimes there are those who fall behind on their taxes, resulting in tax debt. Article 9, paragraph (2) PMK 61/2023 specifically governs the liability of limited liability company directors, wherein the corporate tax debt can be borne personally and/or jointly, including the entire tax debt and tax collection costs. This differs from the responsibility of limited liability company directors as regulated in Law 40/2007, which fundamentally imposes limitations on the accountability of individuals in their positions. As a result, there is ambiguity for corporate managements regarding the limitations of accountability in the tax perspective compared to the corporate law perspective. This research attempts to examine the importance of affirming the legal position of corporate directors as tax debtors. By using normative methods, the author aims to find legal certainty regarding the issues discussed. This research concludes that there is a legal vacuum in regulating the requirements for corporate managements to be exempted from being tax bearers. So that the author recommends that written regulations must be made regarding the understanding of the tax debt insurer for the company's tax debt is limited only to the company's management who is responsible for the company when the tax debt arises. Keywords: Corporate Managements, Tax Debt Insurer, Tax Debt